(untitled) (ARQUISUR Revista, 2022)
The first coastal tourism in Uruguay developed in a particular socio-political framework around 1900. The Montevideo seaside resorts had different origins and routes, but they share some phenomena that allow for interesting cuts of analysis. Among them, this text will scrutinize the incidence of tourism in architectural and urban thought through three thematic episodes that have been treated differently by disciplinary historiography: the coastal public space, hotels and summer chalets. The referred elements that subsist until today are the most durable and enduring traces of the first interactions between architecture and tourism in the country and come to us as a rich heritage legacy.